Oral Bioavailability Enhancement of Sertraline Hydrochloride by Nanoprecipitation and Solvent Diffusion Techniques for Stable Nanosuspension - Pawar, Anil Raosaheb (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The enhancement of oral bioavailability of sertraline (SRT) hydrochloride (HCl) using the nanoprecipitation and solvent diffusion techniques for stable nanosuspension. Materials and Methods: There have been still few of published researches on the formulation of SRT HCl using solid dispersion, fast dissolving tablet, and self-microemulsifying drug delivery systems. Nanosuspension was prepared separately by using different techniques and different polymers (Eudragit RL 100 and PVP K 25). The in vitro dissolution study was performed as per the USP paddle method in 0.1N HCl. The crystalline structure of the drug, the molecular interaction, morphology, and particle size of nanosuspension were also investigated. Results and Discussion: The nanoprecipitation method with drug and PVP K 25 (1:1) showed its potential in the enhancement of the drug release rate (99% in 45 min). The synergistic effects of reduction of drug crystallinity and particle size could increase the dissolution rate of SRT HCl by providing a stable nanosuspension. The in vivo study demonstrated that the maximum plasma concentration and area under the curve values of selected nanosuspension in rabbits were found greater than that of the commercial tablets (tablet potiga, 50 mg) and standard SRT HCl. Conclusion: This work may contribute to a new strategy for enhancement oral bioavailability of SRT HCl.